(untitled) (Bangladesh Journal of Medical Science, 2016)
Lipoma of the oropharynx is an extremely rare entity with less than ten cases reported in so far. We present the case of a 55-year-old gentleman who was referred to our team for an incidental finding of an oropharyngeal mass. Although he did not have stridor despite the mass occupying almost 80% of his oropharynx, he did complain of progressive voice change, feeling of something in the throat and dysphagia over a period of 2 years. The mass was successfully excised endoscopically without the need for a tracheostomy. Airway issues, management options of an oropharyngeal mass, as well as the applied embryology of these lesions are discussed. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.621-623